Racial disparities in Black men with prostate cancer: A literature review - Lillard, James W.; Moses, Kelvin A.; Mahal, Brandon A.; George, Daniel J. (Cancer, 2022)
Black men are disproportionately affected by prostate cancer (PCa), with earlier presentation, more aggressive disease, and higher mortality rates versus White men. Furthermore, Black men have less access to PCa treatment and experience longer delays between diagnosis and treatment. In this review, the authors discuss the factors contributing to racial disparities and present solutions to improve access to care and increase clinical trial participation among Black men with PCa. Racial disparities observed among Black men with PCa are multifaceted, evolving from institutional racism. Cultural factors include generalized mistrust of the health care system, poor physician‐patient communication, lack of information on PCa and treatment options, fear of PCa diagnosis, and perceived societal stigma of the disease. In the United States, geographic trends in racial disparities have been observed. Economic factors, e.g., cost of care, recovery time, and cancer debt, play an important role in racial disparities observed in PCa treatment and outcomes. Racial diversity is often lacking in genomic and precision medicine studies. Black men are largely underrepresented in key phase 3 PCa trials and may be less willing to enroll in clinical trials due to lack of awareness, lack of diversity in clinical trial research teams, and bias of health care providers to recommend clinical research. The authors propose solutions to address these factors that include educating clinicians and institutions on the barriers Black men experience, increasing the diversity of health care providers and clinical research teams, and empowering Black men to be involved in their treatment, which are keys to creating equity for Black men with PCa. Lay summary Prostate cancer negatively affects Black men more than men of other races. The history of segregation and mistreatment in the health care system may contribute to mistrust among Black men. Outcomes are worse for Black men because they are less likely to be screened or to receive treatment for prostate cancer. Black men also are unlikely to participate in clinical research, making it difficult for investigators to understand how Black men are affected by prostate cancer. Suggestions for addressing these differences include teaching physicians and nurses about the issues Black men experience getting treatment and improving how Black men get information on prostate cancer. Racial disparities seen within prostate cancer diagnosis, treatment, and outcomes are multifaceted and evolve from institutional racism. The disparities can be addressed by educating physicians about the barriers faced by Black men receiving health care, identifying the best practices for conveying information on treatments and clinical trials, and increasing diversity among health care professionals.